Influence of elevated temperature on the nutritional profile of Chickpea (Cicer arietinum L.) Seeds - Uday Chand Jha; Marilyn Warburton; Harsh Nayyar; Sadiah Shafi; Ignacio A. Ciampitti; Ashis Ranjan Udgata; Kadambot H. M. Siddique; P. V. Vara Prasad (PLoS ONE, 2025)
Increasing occurrences of episodic heat stress significantly affect crop quality traits, including those of chickpea (Cicer arietinum L.). The adverse effectof heat stress on seed quality was evaluated by cultivating eight chickpea genotypes under non-stress and heat stress conditions, with temperatures set at 25/15°C and 35/20°C, respectively. The genotypes exhibited notable genetic variations in “seed carbon (C, %), protein (%), phosphorus (P, %), potassium (K, %), magnesium (Mg, %), sulfur (S, %), and manganese (Mn, ppm)” concentrations under both conditions. However, no significant variations were observed for seed (S%), seed iron (Fe, ppm), and zinc (Zn, ppm), concentrations under NS conditions or seed copper (Cu, ppm) under heat stress conditions. The genotype (G) × temperature (T) interaction was significant for all traits except for seed K. Correlation analysis revealed positive associations between seed C and protein, seed Mg and P, and seed protein and S under non-stress (NS) conditions. Under heat stress, significant correlations were observed between seed protein and Mg, and seed protein and P. In contrast, significant negative correlations were observed between seed Ca and K under NS conditions and seed Ca and K and seed Fe and Cu under heat stress conditions. The adverse effects of heat stress on nutritional quality and seed yield underscore the necessity for continued research into developing heat-tolerant chickpea cultivars with enhanced seed nutritional traits.